2010
DOI: 10.3109/10428191003728610
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin alfa for the treatment of anemia associated with myelodysplastic syndromes: efficacy and quality of life

Abstract: To evaluate efficacy, safety, changes in biological features, and quality of life (QoL) in low-risk anemic patients with MDS treated with darbepoetin alfa (DPO), 41 patients received DPO 150 microg weekly for 24 weeks. The dose was increased to 300 microg weekly in non-responsive patients. During treatment, 10/17 (59%) transfusion-dependent (TD) and 13/23 (56%) transfusion-free (TF) patients responded. In TF patients, Hb increased from 9.2 +/- 0.9 g/dL to 10.3 +/- 1.4 g/dL by 24 weeks (p = 0.004). The mean res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
5
37
0
Order By: Relevance
“…Several studies have reported a positive correlation between Hb levels and HRQoL [9,19,20,[24][25][26][27][28][29][30][31], although this correlation is not consistent [6]. The current data reinforce the notion of a relationship between Hb levels and QOL-E© as specific patient-reported outcome in MDS patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Several studies have reported a positive correlation between Hb levels and HRQoL [9,19,20,[24][25][26][27][28][29][30][31], although this correlation is not consistent [6]. The current data reinforce the notion of a relationship between Hb levels and QOL-E© as specific patient-reported outcome in MDS patients.…”
Section: Discussionsupporting
confidence: 76%
“…QOL-E© V2.0 data was collected cross-sectionally at baseline in all studies, alongside other measures of clinical effect and HRQoL, such as the EORTC QLQ-C30 questionnaire. Some cross-sectional and longitudinal data have been reported separately [19][20][21][22].…”
Section: Figure 1 Factor Analysis Of the 48-item Draft Qol-e© Instrumentioning
confidence: 99%
“…With this background, it is important to further explore the potentially positive effects of pro-erythroid growth factors in MDS, both on survival and on quality of life. Oliva et al report in the current issue of Leukemia and Lymphoma on 41 patients receiving darbepoetin treatment for MDS-related anemia [10]. The response rate in both transfusion-independent patients and those with a moderate transfusion need was relatively high, 450%, and the study corroborates previous results that treatment is associated with decreased apoptosis of bone marrow progenitors.…”
supporting
confidence: 79%
“…While there is no evidence that ESA use modifies survival, it is associated with improved quality of life. 1618 While ESAs are not contraindicated for individuals with poor PS, poor PS may interfere with the ability to travel to a physician office to receive therapy.…”
Section: Introductionmentioning
confidence: 99%